The Cu, Zn Superoxide Dismutase: Not Only a Dismutase Enzyme - Mondola, Paolo; Damiano, Simona; Sasso, Anna; Santillo, Mariarosaria (Frontiers in Physiology, 2016)
The Cu,Zn superoxide dismutase (SOD1) is an ubiquitary cytosolic dimeric carbohydrate free molecule, belonging to a family of isoenzymes involved in the scavenger of superoxide anions. This effect certainly represents the main and well known function ascribed to this enzyme. Here we highlight new aspects of SOD1 physiology that point out some inedited effects of this enzyme in addition to the canonic role of oxygen radical enzymatic dismutation. In the last two decades our research group produced many data obtained in in vitro studies performed in many cellular lines, mainly neuroblastoma SK-N-BE cells, indicating that this enzyme is secreted either constitutively or after depolarization induced by high extracellular K+ concentration. In addition, we gave many experimental evidences showing that SOD1 is able to stimulate, through muscarinic M1 receptor, pathways involving ERK1/2 and AKT activation. These effects are accompanied with an intracellular calcium increase. In the last part of this review we describe researches that link deficient extracellular secretion of mutant SOD1G93A to its intracellular accumulation and toxicity in NSC-34 cells. Alternatively, SOD1G93A toxicity has been attributed to a decrease of Km for H2O2 with consequent OH. radical formation. Interestingly, this last inedited effect of SOD1G93A could represent a gain of function that could be involved in the pathogenesis of familial Amyotrophic Lateral Sclerosis (fALS).